The role of lining materials in minimizing microleakage in class I cavities restored with nanohybrid composites: an in vitro study lining materials and microleakage in nanohybrid restorations - S. Shenvi; B. K. Aulakh; P. Oswal; A. Khaitan; A. Praveen; K. R. Jadhav (Эндодонтия Today, 2025)
INTRODUCTION. The increasing demand for esthetic dental treatments has led to composite resin restorations becoming the primary material for posterior tooth restorations. However, polymerization shrinkage remains challenging, leading to secondary caries and postoperative discomfort. Liners like resin-modified glass ionomer cement, flowable composites, and Ionosit-Baseliner can mitigate this issue.AIM. To compare the effectiveness of three base liner materials – Ionosit Baseliner, nano-filled flowable composite, and resin-modified glass ionomer cement – in reducing microleakage in Class I cavities restored with nano-hybrid composite resin.MATERIALS AND METHODS. Sixty extracted premolars were prepared with standardized Class I cavities and randomly assigned to three groups (n = 20) based on the applied liner: (1) Ionosit Baseliner, (2) nano-filled flowable composite, and (3) resin-modified glass ionomer cement. Following liner placement, all cavities were restored with a nano-hybrid composite in increments and light-cured. After thermocycling, specimens were coated with nail varnish except for a 1 mm margin around the restoration and immersed in 2.5% methylene blue dye for 24 hours. The teeth were then sectioned and examined under a stereomicroscope at ×40 magnification. Microleakage was scored according to dye penetration depth. Data were analyzed using the Kruskal–Wallis test and post-hoc Dunn’s test (p < 0.05).RESULTS. Ionosit Baseliner demonstrated the lowest median microleakage score [0.00 (IQR: 0.00–0.75)], which was significantly less than both the flowable composite group [2.00 (0.00–3.00), p = 0.0291] and the resin-modified glass ionomer group [2.50 (0.00–4.00), p = 0.0106]. No significant difference was observed between the flowable composite and resin-modified glass ionomer groups (p > 0.9999).CONCLUSIONS. Although none of the tested liners completely eliminated microleakage, Ionosit Baseliner provided significantly better marginal integrity compared to the other liners tested. This suggests that material selection, particularly a liner with lower polymerization shrinkage and appropriate mechanical properties, can improve the longevity and success of posterior composite restorations.